Relationship of thermostability and binding affinity in metal-binding WW-domain minireceptors - Pham, Truc Lam; Conde González, Marcos Rafael; Fazliev, Sunnatullo; Kishore, Agi; Comba, Peter; Thomas, Franziska (ChemBioChem, 2024)
The design of metallo-miniproteins advances our understanding of the structural and functional roles of metals in proteins. We recently designed a metal-binding WW domain, WW-CA-Nle, which displays three histidine residues on its surface for coordination of divalent metals Ni(II), Zn(II) and Cu(II). However, WW-CA-Nle is a molten globule in the apo state and thus showed only moderate binding affinities with Kd values in the μM regime. In this report, we hypothesize that improved thermal stability of the apo state of the metal binding WW-domain scaffold should lead to improved preorganization of the metal-binding site and consequently to higher metal-binding affinities. By redesigning WW-CA-Nle, we obtained WW-CA variants, WW-CA-min and WW-CA-ANG, which were fully folded in the apo states and displayed moderate to excellent thermostabilities in the apo and holo states. We were able to show that the improved thermal stabilities led to improved metal binding, which was reflected in Kd values that were at least one order of magnitude lower compared to WW-CA-Nle. EPR spectroscopy and ITC measurements revealed a better defined and predisposed metal binding site in WW-CA-ANG.